Математична модель багатокритеріальної задачі реінжинірингу фізичних структур розподілених баз даних - Безкоровайний, В. В.; Колесник, Л. В. (My University, 2021)
A mathematical model is proposed for the multi criteria problem of reengineering the physical structures of distributed databases in terms of reduced costs, access time and network traffic. It allows, through the use of universal functions of general utility and utility of particular criteria, to more accurately take into account the preferences of the person making design decisions, and significantly reduce the time complexity of the procedures for calculating scalar estimates
Keywords: автоматизація проектування; інтервальна модель; багатокритеріальна оптимізація; прийняття рішень; реінжиніринг розподілених баз даних